Artigiani a Genova nei secoli XII-XIII - Bezzina, Denise (Reti Medievali E-Book, 2015)
This study differs from the traditional approach to the history of Genoa in the Middle Ages, which is tied to the definition of the ianuensis mercator. On the contrary, it aims at showing aspects of the artisans' life, and therefore at correcting an orientation which has excessively privileged a specific (albeit crucial) sector of the city society. Through a systematic survey of the very rich notary registers, the study traces a multifaceted profile of those belonging to Genoa's trade categories in the 12th and 13th centuries. The first part of the research begins with a definition of the artisans' identity through the analysis of the anthroponymic system, which is then used to illustrate the social and economic dynamics underlying the apprenticeship and wage work. The central part of the book, on the other hand, is dedicated to the commercial and financial tools available to artisans, and to their involvement in long-range trade. The family structure and the social relationships are defined on the basis of a large sample of skills, testaments and quarrels, and then followed by an analysis of the artisans' role in land and real estate transactions. The final discussion focuses on the participation of artisans in the political life and in military activities.